Adult Mortality and Children's Transition into Marriage - Beegle, Kathleen; Krutikova, Sofya (World Bank, Washington, DC, 2012)
Adult mortality due to HIV/AIDS and other diseases is posited to affect children through a number of pathways. On top of health and education outcomes, adult mortality can have significant effects on children by influencing demographic outcomes including the timing of marriage. The authors examine marriage outcomes for a sample of children interviewed in Tanzania in the early 1990s and re-interviewed in 2004. They find that while girls who became paternal orphans married at significantly younger ages, orphanhood had little effect on boys. On the other hand, non-parental deaths in the household affect the timing of marriage for boys